2014
DOI: 10.1007/s12264-013-1408-x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of brain insulin signaling in Alzheimer’s disease

Abstract: Contrary to the previous belief that insulin does not act in the brain, studies in the last three decades have demonstrated important roles of insulin and insulin signal transduction in various functions of the central nervous system. Deregulated brain insulin signaling and its role in molecular pathogenesis have recently been reported in Alzheimer's disease (AD). In this article, we review the roles of brain insulin signaling in memory and cognition, the metabolism of amyloid β precursor protein, and tau phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 149 publications
(137 reference statements)
0
47
0
Order By: Relevance
“…In addition, insulin can attenuate pathogenic binding of Aβ and synaptic deficits (Chen et al 2014). Although insulin mRNA and insulin protein synthesis is not measurable in astrocytes, these glial cells could be influenced by insulin (Henneberger et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, insulin can attenuate pathogenic binding of Aβ and synaptic deficits (Chen et al 2014). Although insulin mRNA and insulin protein synthesis is not measurable in astrocytes, these glial cells could be influenced by insulin (Henneberger et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is critical for memory processing, synaptic genesis and remodeling. Furthermore, insulin is a kind of neuroprotective hormone that contributes not only to metabolism but also to cognition (Chen et al 2014). Several recent reports have indicated that both brain IR density and insulin level decrease with age (Cole and Frautschy 2007; Laron 2009) and many key substrates in the insulin signal transduction pathway are significantly reduced in AD (Liu et al 2011; Pearson-Leary and McNay 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As well as occurring with insulin signaling, it has been found that impairment of cerebral glucose metabolism could occur in the early stages of AD, and deteriorate with the progression of the disease (Shah, Desilva, & Abbruscato, ; Chen, Deng, Zhang, & Gong, ). Compared to peripheral organs, the availability of glucose and other nutrients for neural tissues is limited by the dynamic restrictive properties of the BBB (Chiaravalloti et al, ; Keeney, Ibrahimi, & Zhao, ).…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Insulin is an important long-term neuroprotectant, and severe lack of it leads to neurodegeneration [49]. The brain insulin signaling pathway also offers a promising therapeutic target for treating AD [50]. Intrahippocampal insulin injection in normal rats significantly improves spatial memory ability [51].…”
Section: Insulin Can Improve Cognitive Dysfunction Caused By Insulin mentioning
confidence: 99%